The effectiveness of naphthaleneacetic acid and kinetin on the development of plantlet book cuttings of Chrysanthemum ornamental plants - BUDI, RAHMAD SETIA; PARAMUJI, MUJI; TANJUNG, DENNY AKBAR (Jurnal Natural, 2025)
The high demand for chrysanthemum flowers, coupled with the challenge of acquiring quality seeds in large quantities within a short timeframe, presents significant problems in this study. One potential solution is to propagate plants and utilize plant growth regulators to accelerate their development. Tissue culture techniques, which are essential in agriculture and biotechnology, are employed to produce new plants by isolating, developing, and duplicating specific plant cells or tissues in the laboratory. This study aims to assess the effects of two plant growth regulators Naphthalene Acetic Acid (NAA) and Kinetin on the growth and development of stem cuttings or nodes from ornamental chrysanthemum plants (chrysanthemum) in vitro using MS media. The research utilized a completely randomized design (CRD) factorial approach featuring two treatment factors: NAA and Kinetin. A total of nine treatment combinations were tested, with NAA concentrations of 0.5, 1.0, and 1.5 ml L-1, and Kinetin concentrations of 1, 2, and 3 ml L-1. Each treatment was repeated three times. Observations included measurements of plant height, leaf count, root count, and wet weight. The best results for each parameter were observed in treatment K3N2, which yielded a plant height of 30.73 mm and an average of 18.33 leaves. The optimal results for root count and wet weight were found in treatment K3N3, which produced an average of 13.83 roots and 3.57 grams, respectively. Overall, increasing the concentrations of NAA and Kinetin positively influenced all parameters evaluated.